Muscle mineral profile of water buffaloes (Bubalus bubalis) reared in different production systems of the Brazilian Eastern Amazon - Laurena Silva Rodrigues; Jamile Andréa Rodrigues da Silva; José de Brito Lourenço-Júnior; André Guimarães Maciel e Silva; André Martinho de Almeida; Miguel Pedro Mourato; Vinícius Costa Gomes de Castro; Andréia Santana Bezerra; Welligton Conceição da Silva; José António Mestre Prates; José António Mestre Prates (Frontiers in Veterinary Science, 2023)
Healthy food must have an adequate balance of macroelements, such as calcium or phosphorus and, microelements, such as iron, copper. This study aimed to evaluate the influence of three extensive systems, during the dry and rainy seasons, and an intensive (feedlot) system in the Eastern Amazon, on the muscle mineral profile of water buffaloes. In total, 12 male buffaloes, aged between 24 and 36 months, slaughtered in commercial slaughterhouses, were used in each of the systems considered: Marajó island, Santarém, Nova Timboteua, and a feedlot. Approximately 5 g of muscle was collected, stored, and frozen, until freeze-dried. The samples were analyzed for the mineral profile using inductively coupled plasma-optical emission spectrometry (ICP-OES). There were significant differences (P < 0.05) for concentrations of sodium (Na), magnesium (Mg), phosphorus (P), sulfur (S), copper (Cu), zinc (Zn), and iron (Fe). Extensive and intensive systems showed significant differences (P < 0.05) for Na, Ca, S, Cu, and Fe concentrations. The season also influenced (P < 0.05) K, Ca, P, S, Zn, and Fe concentrations. The location and season of the year had a significant interaction (P < 0.05) for K, Mg, P, Zn, and Fe concentrations. The study showed that the different Amazonian production systems and the year season influenced the levels of minerals present in buffalo muscle. The values obtained were, in general, higher in extensive production systems, and Marajó Island stood out with higher mineral values in the dry season. Therefore, the meat from animals reared in these systems is a good mineral source for daily human needs.